Optimal wavenumber as function of A (Re=2000,Wo=15) - Duo Xu; Baofang Song; Marc Avila (PANGAEA, 2022)
The data are obtained via an in-house Matlab script (developed by Dr. Baofang Song) to compute the non-modal transient growth of disturbances in pulsatile and oscillatory pipe flows. In this study, a Newtonian fluid driven by pulsatile and oscillatory flow rate flows in a straight pipe. In pulsatile flow, there are three governing parameters: steady Reynolds number (defined by the steady flow component), pulsation amplitude (ratio of oscillatory and steady flow component) and Womersley number (dimensionless pulsation and oscillation frequency). In oscillatory flow, due to vanishment of steady flow component, oscillatory Reynolds number (defined by the oscillation flow component) and Womersley number. The Reynolds number defined by the thickness of Stokes layer is alternatively used for the oscillatory Reynolds number. The study was carried out in a manner that one governing parameter varies while other governing parameters are fixed. The data file extquotesinglewavenumber_A_Wo15.dat extquotesingle shows the dependence of the optimal wavenumber on the pulsation amplitude. This file includes three columns: the first column indicates the pulsation amplitude; the second column indicates the optimal axial wavenumber; the third column indicates the optimal azimuthal wavenumber (corresponding to the maximum energy amplitude).